Evaluation and Management of Atopic Dermatitis - Kirubakaran, J John; Surekha, Khandavilli Lakshmi; Manasa, Saka; Chakra Satyanarayana, Amarthi Naga Venkata; Srilakshmi, KV; Palivela, Harinath; Kumar, Praveen; Dhanaraju, Magharla Dasaratha (Indian Journal of Pharmacy Practice)
Background: Atopic dermatitis is the most predominant disease seen mostly in children and the prevalence of disease is 10% to 20%. The pathogenesis of the disease includes immunological, food allergies, pollen grains, breast feeding and secondary infections. Objectives: To identify the cause and to evaluate the appropriate treatment of the patients with atopic dermatitis. Methods: A total of 116 patients are included in the study conducted in skin care and paediatric hospital in the area of Rajahmundry, India. Results: From the study conducted, we observed that the occurrence of the disease is in different age groups and most of the patients are affected by pollen grains (10%) followed by pets and respiratory illness (5.3%), allergies (5%) and pollutants (4.6%) and family history (3.3%) respectively. On evaluation, the treatment topical steroids are found to be more prominently used followed by emollients, antibiotics, antihistamines and immunomodulators. Conclusion: As per the study, we conclude that the occurrence of the disease is mainly due to pollen grains followed by other determined causes as seen in the area of Rajahmundry.
Keywords: Atopic dermatitis; Aetiology; Pollen grains; Topical steroids; Emollients.